KEGIATAN KHITOBAH SEBAGAI PENGEMBANGAN PUBLIC SPEAKING PADA SANTRI PONDOK PESANTREN MIFTAHUL KHAIRAT - Dewi Robiatul Adawia; Wisri; Aminul `Alimin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
Miftahul Khairat Islamic Boarding School, established in 2009, is a religious educational institution dedicated to developing the potential of its students (santri) in both Islamic scholarship and non-academic skills. One of the activities implemented to foster this potential is khitobah—public speaking practice. This activity aims to cultivate courage and communication skills while shaping students into confident individuals capable of effective religious outreach (dakwah). This study employs a qualitative case study approach, gathering data through observation, interviews, and document analysis. Data collection commenced in February 2025. The findings indicate that the khitobah activity at Miftahul Khairat Islamic Boarding School is a vital component of the educational system; it serves not merely a ceremonial function but plays a strategic role in character development, particularly regarding courage, responsibility, and communication abilities. Through sessions held twice weekly, students are guided to structure and deliver Islamic content, thereby honing their dakwah skills and their ability to communicate knowledge effectively.